Efficient Assured Cloud Data Deletion and Verification Scheme Using AES-XOR Encryption and Merkle Trees - Huda Sharaf Eldin Shakur; Baban Ahmed Mahmood (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2026)
With the increasing interest of cloud computing users in storing and processing their data, the need for secure and permanent data deletion has grown. This research paper proposes a practical, evaluable, and testable mechanism for verifying data integrity and ensuring its deletion. The proposed system integrates sequential XOR technology with AES-based block-level encryption, thereby achieving strong interconnection between encrypted blocks. This prevents block separation, decryption, or tampering during transmission and storage. The encryption key is divided into independent parts, the purpose of which is to prevent any single party from possessing the complete encryption key. This ensures that the file cannot be recovered if any part of the key is deleted. The encrypted blocks are then arranged with one of the key parts in a Merkel tree structure to guarantee data integrity and verifiability during storage and retrieval. Through experimentation and providing similar levels of confidentiality and data recovery, the experimental results showed that this mechanism achieves competitive computing efficiency with reasonable storage and communication costs compared to basic methods. This solution was implemented on a real cloud platform within the Microsoft Azure environment, proving its feasibility, security and reliability without the need for major modifications to the existing cloud infrastructure.